STRATEGI BRANDING WISATA CANDI SOJIWAN UNTUK MENINGKATKAN KUNJUNGAN WISATA - Rahmawati, Athaya Dea; Kismartini, Kismartini; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The government and Pokdarwis Gendewa formulated and implemented a branding strategy as an alternative to increase tourist visits to Sojiwan Temple. The objectives of this study are, first, to describe and analyze the branding strategy to increase tourist visits to Sojiwan Temple. Second, describe and analyze the driving and inhibiting factors of branding strategies to increase tourist visits to Sojiwan Temple. This research uses qualitative methods with descriptive analysis accompanied by relevant supporting evidence. This research was conducted at the Central Java-DIY Region X Cultural Preservation Center; Klaten Regency Tourism, Culture, Youth and Sports Office; and at Kebondalem Kidul Village Hall. The results of this study are the branding strategy of Sojiwan Temple tourism through image formation by creating a slogan/tagline, namely sanjiwana, then the slogan is communicated through social media and cultural festivals. Supporting factors for the Sojiwan Temple tourism branding strategy are clear regulations, the government's vision and mission, clear targets and objectives, and an agreement through the MoU. The inhibiting factor of the branding strategy is the lack of communication between the government and related parties. The recommendations given are to create a visual design (logo) based on the tagline as the identity of Sojiwan Temple tourism, create personal social media so that branding communication is more effective, and collaboration between the government and related parties so that the implementation of branding can be done well.